Global existence results for neutral functional differential inclusions with state-dependent delay - Alaidarous, E.; Benchohra, M.; Medjadj, I. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We consider the existence of global solutions for a class of neutral functional differential inclusions with state-dependent delay. The proof of the main result is based on the semigroup theory and the Bohnenblust – Karlin fixed point theorem.